Gender Inequality, Female Leadership and Aid Allocation: A Panel Analysis of Aid for Education. (9th March 2016) - Kleemann, Linda; Nunnenkamp, Peter; Thiele, Rainer
Abstract: This paper contributes to the aid allocation literature by assessing whether recipient countries with persistent gender inequality in schooling receive more aid for education. Furthermore, we analyze whether female leadership of the relevant ministries in the donor countries results in better targeted aid by directing aid for education to where girls receive less schooling than boys. Our empirical findings suggest that female as well as male leaders have rewarded countries with more years of schooling of all children, or specifically of girls, rather than allocating aid for education according to general or gender‐specific needs with regard to schooling. Female leadership appears to have played a marginal role in the allocation of aid for education. © 2016 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.